2021
DOI: 10.1093/socpro/spab054
|View full text |Cite
|
Sign up to set email alerts
|

Crafting Charismatic Cops: Community Policing and the Faulty Reputations Paradigm

Abstract: This article draws on theories of reputation to analyze community policing’s role in managing perceptions of the police. Drawing on longitudinal interviews and fieldwork that followed the implementation of a community policing program, this article analyzes how officers interpret, manage, and attempt to reconstruct police reputation in their everyday work. I argue that police understand reputation through a lens I call the “faulty reputations paradigm”, an expectation that most negative perceptions about the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…At the same time, it is also important to note that public expectations about the roles that police departments play in society extend well beyond crime control. Since at least the early 1990s, municipal police departments throughout the United States have regularly engaged in "community policing" activities that involve nonenforcement contact and cooperation with the public on matters that are, at best, only indirectly related to crime reduction (Cheng, 2020;Peyton et al, 2019;Rivera-Cuadrado, 2021). Perhaps unsurprisingly, national surveys fielded in the aftermath of Floyd's murder showed that majorities were opposed to reductions in spending on police services in general, but also believed officers should continue to play a role in a variety of specific tasks, ranging from vehicle stops to community engagement activities like youth outreach, even if supplemented by social service workers (e.g., Pew, 2020; Peyton et al, 2020).…”
Section: The Relationship Between Public Opinion and Criminal Justice...mentioning
confidence: 99%
“…At the same time, it is also important to note that public expectations about the roles that police departments play in society extend well beyond crime control. Since at least the early 1990s, municipal police departments throughout the United States have regularly engaged in "community policing" activities that involve nonenforcement contact and cooperation with the public on matters that are, at best, only indirectly related to crime reduction (Cheng, 2020;Peyton et al, 2019;Rivera-Cuadrado, 2021). Perhaps unsurprisingly, national surveys fielded in the aftermath of Floyd's murder showed that majorities were opposed to reductions in spending on police services in general, but also believed officers should continue to play a role in a variety of specific tasks, ranging from vehicle stops to community engagement activities like youth outreach, even if supplemented by social service workers (e.g., Pew, 2020; Peyton et al, 2020).…”
Section: The Relationship Between Public Opinion and Criminal Justice...mentioning
confidence: 99%